The Evaluation of the Efficacy of the R&D European Funds in Piedmont - Davide Fantino; Giusy Cannone (European Regional Science Association (ERSA), 2011)
This paper provides some empirical evidence of the impact of two policy measures, aiming at supporting innovative activity of small and medium firms in Piedmont. Both measures use European Structural Funds, but are managed at a regional level. Measure 2.1b, a concessional loan aiming at stimulating the introduction of innovative plants, machinery and equipments, had positive effects on investments, assets and sales in the short run; but there are hints that investments could have been anticipated from already scheduled projects in the following periods. Measure 2.6b, a free grant aiming at stimulating research activity of firms, had positive effects on intangible investments and capital, but this new knowledge does not seem to be able to directly impact on the production process of the firm. When evaluating the effect for specific groups of firms, for both measures we do not find stronger effects for firms characterized by a high intensity of subsidy. When considering firms with a high cost of capital, we find that Measure 2.1b significantly reduced the interest rate asked by the lenders also after the end of the project, while Measure 2.6b had not been effective at all.
Keywords: 330